Structurally Flexible 2D Spacer for Suppressing the Electron–Phonon Coupling Induced Non-Radiative Decay in Perovskite Solar Cells - Cao, Ruikun; Sun, Kexuan; Liu, Chang; Mao, Yuhong; Guo, Wei; Ouyang, Ping; Meng, Yuanyuan; Tian, Ruijia; Xie, Lisha; Lü, Xujie; Ge, Ziyi (Nano-Micro Letters, 2024)
This study presents experimental evidence of the dependence of non-radiative recombination processes on the electron–phonon coupling of perovskite in perovskite solar cells (PSCs). Via A-site cation engineering, a weaker electron–phonon coupling in perovskite has been achieved by introducing the structurally soft cyclohexane methylamine (CMA+) cation, which could serve as a damper to alleviate the mechanical stress caused by lattice oscillations, compared to the rigid phenethyl methylamine (PEA+) analog. It demonstrates a significantly lower non-radiative recombination rate, even though the two types of bulky cations have similar chemical passivation effects on perovskite, which might be explained by the suppressed carrier capture process and improved lattice geometry relaxation. The resulting PSCs achieve an exceptional power conversion efficiency (PCE) of 25.5% with a record-high open-circuit voltage (VOC) of 1.20 V for narrow bandgap perovskite (FAPbI3). The established correlations between electron–phonon coupling and non-radiative decay provide design and screening criteria for more effective passivators for highly efficient PSCs approaching the Shockley–Queisser limit. Highlights: 1 The soft 2D material reduces the coupling strength between carriers and longitudinal optical phonons, releasing the mechanical stress of lattice vibration. 2 The power conversion efficiency of rigid devices and flexible devices reaches 25.5% and 23.4%, respectively.